2015
DOI: 10.1021/acs.accounts.5b00244
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Synthesis of More Reactive S = 2 Non-Heme Oxoiron(IV) Complexes

Abstract: Conspectus2003 marked a banner year in the bioinorganic chemistry of mononuclear non-heme iron enzymes. The first non-heme oxoiron(IV) intermediate (called J) was trapped and characterized by Bollinger and Krebs in the catalytic cycle of taurine dioxygenase (TauD), and the first crystal structure of a synthetic non-heme oxoiron(IV) complex was reported by Münck, Nam, and Que. These results stimulated inorganic chemists to synthesize related oxoiron(IV) complexes to shed light on the electronic structures and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
189
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(200 citation statements)
references
References 67 publications
(157 reference statements)
4
189
0
1
Order By: Relevance
“…Many non-heme enzymes and synthetic complexes adopt the alternative approach of using weak field ligands to generate a high-spin ferryl active oxidant [10]. Comparisons of synthetic iron(IV) ferryl species with S = 1 and S = 2 ground states have shown that the latter are consistently more reactive towards H • atom abstraction from a substrate [4,11]. Such considerations can also have a bearing on organometallic catalysis, where first-row transition ions are increasingly playing a role [12].…”
Section: Methodsmentioning
confidence: 99%
“…Many non-heme enzymes and synthetic complexes adopt the alternative approach of using weak field ligands to generate a high-spin ferryl active oxidant [10]. Comparisons of synthetic iron(IV) ferryl species with S = 1 and S = 2 ground states have shown that the latter are consistently more reactive towards H • atom abstraction from a substrate [4,11]. Such considerations can also have a bearing on organometallic catalysis, where first-row transition ions are increasingly playing a role [12].…”
Section: Methodsmentioning
confidence: 99%
“…Investigation of literature revealed that homolytic cleavage of oxygen-oxygen bond leads to the formation Fe IV =O species whereas heterolytic cleavage of the same gives rise to Fe V =O species. The reaction condition and ligand frame involved with iron are responsible for homolytic or heterolytic cleavage and concomitant formation of corresponding oxo species as intermediate [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising approaches is based on hypervalent transition‐metal oxo complexes 1, 2. An important advantage of using transition metals and their oxo complexes is the potential they offer to explore multistate reactivity 3, 4, 5, 6.…”
mentioning
confidence: 99%